Characterisation of the unstable expanded CAG repeat in the MJD1 gene in four Brazilian families of Portuguese descent with Machado-Joseph disease. Issue 10 (October 1995) - Stevanin, Giovanni; Cassa, Eloy; Cancel, Géraldine; Abbas, Nacer; Dürr, Alexandra; Jardim, Edymar; Agid, Yves; Sousa, Patricia S; Brice, Alexis
Abstract : Machado-Joseph disease (MJD) is an autosomal dominant neurodegenerative disorder which has been shown to result, in Japanese families, from the expansion of a CAG repeat in the MJD1 gene on chromosome 14q. We show that the same molecular mechanism is responsible for MJD in four large Brazilian kindreds of Portuguese descent. The behaviour of the mutation was evaluated in 28 affected and 19 asymptomatic gene carriers. The number of repeats in the expanded alleles ranged from 66 to 77 with a strong negative correlation with age at onset (r=0·79). A mean 1·6 repeats increase from generation to generation correlated with clinical anticipation. Instability of the CAG repeat was bidirectional, with expansions as well as contractions, and was more marked in paternal transmissions. Finally, linkage disequilibrium was complete at locus D14S280 in the four Portuguese-Brazilian kindreds and four previously reported French families with the same mutation, which suggests the existence of a common founder.